Isolasi dan Uji Aktivitas Anti Bakteri Fungi Endofit Bunga Cengkeh (Syzygium aromaticum L.) dalam Menghambat Bakteri Penyebab Karies Gigi - Adelina, Nabila; Fitriana, Fitriana; Naid, Tadjuddin; Seniwati, Seniwati; Septiyanti, Septiyanti (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Clove is one of the plants that has the potential as an antibacterial. Clove, besides being known as a food flavoring, also has properties as an analgesic, bacteriostatic, and treat stomach cramps. This study aims to isolate and obtain a chromatogram profile of clove flowers (Syzygium aromaticum L.) against bacteria that cause dental caries infection. The search for bioactive compounds in this study was to isolate endophytic fungi in clove flowers and then purified and tested macroscopically. Then a screening test was carried out and then continued for 21 days fermentation using Potato Dextrose Broth medium to separate the supernatant and mycelia, then extracted using ethyl acetate solvents to obtain ethyl acetate extract. Antibacterial activity testing was carried out by TLC-Bioutography method using ethyl acetate: n-hexane (4: 1) eluent. The results of this study obtained five endophytic fungi isolates that were active against the bacteria Streprococcus mutans and Porphyromonas gingivalis. Isolates that have the greatest activity, namely isolates with the code IFBC-01. The results of TLC-Bioautography obtained one speck with a value of rf: 0.67 which means it has antibacterial activity.